2002
DOI: 10.1002/1099-0682(20021)2002:1<153::aid-ejic153>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

The Insertion of Heterocumulenes into Zn−H and Zn−OH Bonds of Pyrazolylborate−Zinc Complexes

Abstract: The pyrazolylborate−zinc complexes TpPh,MeZn−H and TpPh,MeZn−OH undergo insertion reactions with heterocumulenes. CO2, CS2 and RNCS insert into the Zn−H function to yield the corresponding Zn−OCH(O), Zn−SCH(S) and Zn−SCH(NR) complexes. The primary products resulting from the insertion of CS2, COS and RNCS into the Zn−OH function undergo rearrangements and subsequent reactions. TpPh,MeZn−OH and CS2 or COS yield TpPh,MeZn−SH and COS or CO2, whereas with RNCS the complexes TpPh,MeZn−SC(O)NHR are formed. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 32 publications
5
38
0
2
Order By: Relevance
“…[1] For example, one of the simple Zn-enzymecatalyzed processes, the hydration of CO 2 by carbonic anhydrase, has led to extensive mechanistic and theoretical studies of the interaction of CO 2 with Zn-OH. [2][3][4][5] Also, in heterogeneous catalysis, a detailed understanding of the surface chemistry of CO 2 is an important issue; interest in this topic ranges from developing new processes for an emplacement of this greenhouse gas to the synthesis of methanol from syngas (CO/CO 2 /H 2 ) over Cu/ZnO catalysts. [6] Numerous studies have been reported on CO 2 adsorption on clean metal surfaces, where frequently activation is found to occur via the formation of a bent CO 2 dÀ species.…”
mentioning
confidence: 99%
“…[1] For example, one of the simple Zn-enzymecatalyzed processes, the hydration of CO 2 by carbonic anhydrase, has led to extensive mechanistic and theoretical studies of the interaction of CO 2 with Zn-OH. [2][3][4][5] Also, in heterogeneous catalysis, a detailed understanding of the surface chemistry of CO 2 is an important issue; interest in this topic ranges from developing new processes for an emplacement of this greenhouse gas to the synthesis of methanol from syngas (CO/CO 2 /H 2 ) over Cu/ZnO catalysts. [6] Numerous studies have been reported on CO 2 adsorption on clean metal surfaces, where frequently activation is found to occur via the formation of a bent CO 2 dÀ species.…”
mentioning
confidence: 99%
“…The active site is proposed to contain a Zn atom in a tetrahedral coordination sphere connected to histidine ligands. Model studies [44,45] have so far activated CO 2 , but the process stopped at the bicarbonate complex (''product inhibition''). Figure 17 is an illustration of the Zn-complex from Ref.…”
Section: Example Reaction-anhydrasementioning
confidence: 99%
“…Die Aktivierung von CO 2 ist eines der wichtigsten Themen in der Katalyse 1. So wurden zum Beispiel zur Hydratation von CO 2 durch Carboanhydrase, einem der einfachen durch Zinkenzyme katalysierten Prozesse, umfangreiche mechanistische und theoretische Studien durchgeführt, speziell zur Wechselwirkung von CO 2 mit ZnOH 25. Auch in der heterogenen Katalyse ist ein grundlegendes Verständnis der Oberflächenchemie von CO 2 von großer Bedeutung; das Interesse reicht von der Entwicklung neuer Prozesse für eine Einlagerung dieses Treibhausgases bis zur Methanolsynthese aus Synthesegas (CO/CO 2 /H 2 ) über Cu/ZnO‐Katalysatoren 6.…”
Section: Experimentelle Und Berechnete Schwingungsfrequenzen [Cm−1] Dunclassified